Protein damage, repair and proteolysis - YILMAZ, BETÜL (ELSEVIER, 2014)
Proteins are continuously affected by various intrinsic and extrinsic factors. Damaged proteins influence several intracellular pathways and result in different disorders and diseases. Aggregation of damaged proteins depends on the balance between their generation and their reversal or elimination by protein repair systems and degradation, respectively. With regard to protein repair, only few repair mechanisms have been evidenced including the reduction of methionine sulfoxide residues by the methionine sulfoxide reductases, the conversion of isoaspartyl residues to L-aspartate by L-isoaspartate methyl transferase and deglycation by phosphorylation of protein-bound fructosamine by fructosamine-3-kinase. Protein degradation is orchestrated by two major proteolytic systems, namely the lysosome and the proteasome. Alteration of the function for both systems has been involved in all aspects of cellular metabolic networks linked to either normal or pathological processes. Given the importance of protein repair and degradation, great effort has recently been made regarding the modulation of these systems in various physiological conditions such as aging, as well as in diseases. Genetic modulation has produced promising results in the area of protein repair enzymes but there are not yet any identified potent inhibitors, and, to our knowledge, only one activating compound has been reported so far. In contrast, different drugs as well as natural compounds that interfere with proteolysis have been identified and/or developed resulting in homeostatic maintenance and/or the delay of disease progression. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aging; Lon protease; Lysosome; Methionine sulphoxide reductase; Protein modification; Ubiquitin-proteasome system; METHIONINE-SULFOXIDE-REDUCTASE; UBIQUITIN-PROTEASOME SYSTEM; NF-KAPPA-B; LOW-DENSITY-LIPOPROTEIN; LIFE-SPAN EXTENSION; METAL-CATALYZED OXIDATION; AGE-RELATED-CHANGES; L-ISOASPARTYL METHYLTRANSFERASE; GLYCATION END-PRODUCTS; ATP-DEPENDENT PROTEASE